SMEs: between the application of governance mechanisms and the problem of administrative corruption -Field Study (Journal of Economic Additions, 2020)
This study aims to highlight the importance of SMEs in creating and developing a modern and dynamic knowledge-based economy, because of their ability to promote entrepreneurship and entrepreneurial skills and because of their ability to be flexible and adapt quickly to the changing market, and to Creating new jobs, making a significant contribution to innovation and supporting regional development and social cohesion, as well as making a significant contribution to GDP growth and creating new jobs, and addressing the problem of administrative corruption that hinders the development and development of such sensitive institutions, has also been addressed. The study found that there is an inverse relationship between organizational governance mechanisms and corruption, which means that the more governance mechanisms are applied within SMEs, the less corruption there is.Keywords: SMEs, administrative corruption, corporate governance, Balanced strategic performance.Jel Classification Codes: G 39, C12.